If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(-x)-2(-x)-(-4)=(-x)-x+1
We move all terms to the left:
3(-x)-2(-x)-(-4)-((-x)-x+1)=0
We add all the numbers together, and all the variables
3(-1x)-2(-1x)-((-1x)-x+1)-(-4)=0
We add all the numbers together, and all the variables
3(-1x)-2(-1x)-((-1x)-x+1)+4=0
We multiply parentheses
-3x+2x-((-1x)-x+1)+4=0
We calculate terms in parentheses: -((-1x)-x+1), so:We add all the numbers together, and all the variables
(-1x)-x+1
We add all the numbers together, and all the variables
-1x+(-1x)+1
We get rid of parentheses
-1x-1x+1
We add all the numbers together, and all the variables
-2x+1
Back to the equation:
-(-2x+1)
-1x-(-2x+1)+4=0
We get rid of parentheses
-1x+2x-1+4=0
We add all the numbers together, and all the variables
x+3=0
We move all terms containing x to the left, all other terms to the right
x=-3
| 2(y−56)=60 | | x^2−2x−24=0 | | 96=6(n+2) | | 3-4r=-25 | | x^2−2^x−24=0 | | 5r^=80 | | 48=4(h+72) | | h2-3h=8 | | 12.3=41x | | -15-y=31 | | 2p-3.7=2.3 | | 5/6x+2/3=1/2x-10/3 | | 4(u+100)=0 | | 44=9n+8 | | -5(m+32)=-75 | | 6(u+6)=90 | | h/3+8=15 | | 3.6/x=-5 | | 16-y=25 | | -2=4+n/9 | | 5w+2w^2=42 | | 10k+6=3k+34 | | 2(8)+2y=72 | | 2/x=5/2x-1 | | -9=m/3-7 | | 8v+1=70v-20 | | x/1-x=2.26 | | 2(8)+2l=72 | | 3x+9=x+25 | | 2s-19=27 | | 2s−19=27 | | -p+10=1 |